Umbilical cord milking-benefits and risks - Koo, Jenny; Kilicdag, Hasan; Katheria, Anup (Frontiers in Pediatrics, 2023)
The most common methods to provide additional placental blood to a newborn are delayed cord clamping (DCC) and umbilical cord milking (UCM). Concerns with DCC include the potential risk of hypothermia from extended exposure to the cold environment in the operating room or delivery room and a delay in performing resuscitation. UCM has been studied as a possible alternative for DCC as it allows for immediate resuscitation after birth. However, the safety profile of UCM, particularly in premature newborns, remains a concern. This review will highlight the currently known risks and benefits of umbilical cord milking and explore ongoing studies.